Close Cathode Chamber technology for cosmic particle tracking. (July 2015) - Oláh, László; Barnaföldi, Gergely Gábor; Hamar, Gergő; Melegh, Hunor Gergely; Surányi, Gergely; Varga, Dezső
Abstract: The Close Cathode Chamber (CCC) technology has been developed and found useful in a portable tracking system under harsh and varying environmental conditions due to their mechanical and operational stability. The muon flux have been measured on ground and at shallow depths underground (< 70 m.r.e.) which provides a good reference for other experiments. The multiple scattering in rock and the soft contamination of the track sample have been investigated experimentally and by GEANT4. The applicability of the sensor to detect underground rock density inhomogeneities has been demonstrated via reconstruction of an underground tunnel system. A modified muon tomograph has been built with sensitive area of 0.25 m 2 and angular resolution of 15 mrad which is useful for material discrimination via the measurement of multiple scattering and absorption of muons. The reliable tracking performance, low power consumption and fair angular resolution make the CCC technology useful also in large area tracking detectors.